1999
DOI: 10.1159/000054443
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gonadal and Somatotropic Axis by Chronic Intraventricular Infusion of Insulin-Like Growth Factor 1 Antibody at the Initiation of Puberty in Male Rats

Abstract: There has been increasing experimental evidence to suggest that insulin-like growth factor 1 (IGF-I) may be one of the essential regulators in the reproductive system of the rat. IGF-I is synthesized in the hypothalamus and IGF-I immunoreactivity increases during puberty. Consequently we hypothesized that centrally located IGF-I might contribute to the initiation of puberty. Centrally located IGF-I was immunoneutralized to assess this hypothesis. Male Wistar rats, 28 days old, were infused intracerebroventricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Prepubertal rats receiving intracerebroventricular IGF-1 experienced an earlier pubertal onset, as indicated by vaginal opening, than rats given saline (7). In agreement with this finding, male rats given intracerebroventricular IGF-1 antibody experienced puberty, as indicated by serum testosterone level and testicular weight, significantly later than rats given vehicle (8). Female mice with deletion of the growth hormone receptor experience delayed puberty, as indicated by vaginal opening, that is advanced by IGF-1 administration (9).…”
Section: Introductionsupporting
confidence: 74%
“…Prepubertal rats receiving intracerebroventricular IGF-1 experienced an earlier pubertal onset, as indicated by vaginal opening, than rats given saline (7). In agreement with this finding, male rats given intracerebroventricular IGF-1 antibody experienced puberty, as indicated by serum testosterone level and testicular weight, significantly later than rats given vehicle (8). Female mice with deletion of the growth hormone receptor experience delayed puberty, as indicated by vaginal opening, that is advanced by IGF-1 administration (9).…”
Section: Introductionsupporting
confidence: 74%
“…Zhen et al (33) showed that IGF-I increased the expression of gonadotropin-releasing hormone in vitro. Although the intracerebroventricular administration of IGF-I antibodies resulted in delayed puberty in male rats (34), intraventricular injections of IGF-I advanced puberty in female rats (35). In contrast, a recent study of 76 prepubertal girls showed an inverse correlation between IGF-I and 25(OH)D (36).…”
Section: Discussionmentioning
confidence: 91%
“…In several species, including man, monkey, rat and mouse [1, 8, 13, 21], female puberty is associated with a GH-induced increased expression of IGF-1 in the liver on the morning of the first proestrus, resulting in increased levels of serum IGF-1, which peak during proestrus afternoon accompanied by increases in serum LH, FSH, and E 2 [4, 6, 9]. Both peripherally and centrally derived IGF-1 can accelerate the onset of puberty in juvenile rats, via a stimulation of the GnRH release [4].…”
Section: Discussionmentioning
confidence: 99%
“…Around puberty the plasma level of IGF-1 increases due to an elevated hepatic IGF-1 gene expression and production, induced by the also increasing GH level [4,5,6]. In prepubertal rats IGF-1 of peripheral origin directly acts on GnRH neurons and affects GnRH synthesis and release [1, 4,6,7,8]. Absence of IGF-1 delayed normal maturation in male and female mice [1, 9], whereas ventricular infusion (i.c.v.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation